MULTIDIMENSIONAL EFFECTS OF SHIRODHARA ON PSYCHO-SOMATIC AXIS IN THE MANAGEMENT OF PSYCHO-PHYSIOLOGICAL DISORDERS - N. Dornala, Sathya; SN Dornala, Snehalatha (International Journal of Ayurveda and Pharma Research, 2015)
Now-a-days many clinical conditions of different physiological systems becoming psychosomatic in nature, may be because of modern day living. Psychosomatic disorders represent a therapeutic enigma. Despite compelling evidence to suggest the integrity of mind and body, humans are famously prone to experiencing them as separate. Ayurveda essentially sees every disease as a psychosomatic manifestation and views the mind and body as two aspects of one unity. Considering the involvement of Hypothalamico-Pituitary-Adrenal Axis (HPA Axis) in most of the psychosomatic disorders; an attempt is made to use the word Psychosomatic axis in synonymous with HPA axis/Shatchakras. Shirodhara, an icon of Ayurveda in global scenario, is the pouring of warm herbal oil over the forehead in a pendulous manner. This treatment rejuvenates the nervous system, releases emotions, opens the subtle channels and unfolds bliss throughout the mind and body. This paper explores the advanced understanding of Shirodhara and its role in prevention and treatment of psychosomatic disorders and promotion of mental health & in turn to emphasize its importance in current day practice.